Comparative study of the physicochemical, nutritional, and antioxidant properties of some commercial refined and non-centrifugal sugars. (July 2018) - Lee, Jong Suk; Ramalingam, Srinivasan; Jo, Il Guk; Kwon, Ye Som; Bahuguna, Ashutosh; Oh, Young Sook; Kwon, O-Jun; Kim, Myunghee
Abstract: Three refined and four unrefined branded commercial sugars available in Korea were investigated in terms of pH, soluble solids, moisture, ash content, turbidity, color values, microbial profile, reducing power, 2, 2-diphenyl-1-picrylhydrazyl and 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activities, cellular antioxidant activity, and total phytoconstituent ( i.e. phenolic, flavonoid, mineral, sucrose, glucose, and fructose) contents using standard analytical protocols such as high-performance liquid chromatography, gas chromatography-flame ionization detector/mass spectrometry, and inductively coupled plasma atomic emission spectroscopy. All tested physicochemical parameters were within the recommended standard levels. Significantly high nutritional and antioxidant properties were observed for the unrefined sugars, especially AUNO® sugar, whereas a high sucrose content was detected for the refined sugars. Hence, this study revealed that the degree of purification affects the nutritional values and antioxidant potentials of sugars. The present findings also indicate that unrefined sugars can be used as sweeteners in sugar-based cuisine to obtain nutritional and antioxidant-rich foodstuff. Graphical abstract: Highlights: Refining process affects the nutritive and antioxidant properties of sugars. Physicochemical characters of analyzed sugars are within the recommended range. The absence of microbes indicates the outstanding hygiene of tested sugars. Cellular antioxidant actives of commercial sugars were evaluated. Unrefined sugars contain health beneficial and sensory compounds.